A NOTE ON THE SYRIAC VERSION OF ATHANASIUS' AD EPICTETUM IN MS. B.M. ADD. 14557 - Ebied, R. Y. (The journal of theological studies, 1972)
R. Y. EBIED, L. R. WICKHAM; A NOTE ON THE SYRIAC VERSION OF ATHANASIUS' AD EPICTETUM IN MS. B.M. ADD. 14557, The Journal of Theological Studies, Volume XXIII, I